The Vocal Repertoire of Pale Spear-Nosed Bats in a Social Roosting Context - Lattenkamp, Ella Z.; Shields, Stephanie M.; Schutte, Michael; Richter, Jassica; Linnenschmidt, Meike; Vernes, Sonja C.; Wiegrebe, Lutz (Frontiers in Ecology and Evolution, 2019)
Commonly known for their ability to echolocate, bats also use a wide variety of social vocalizations to communicate with one another. However, the full vocal repertoires of relatively few bat species have been studied thus far. The present study examined the vocal repertoire of the pale spear-nosed bat, Phyllostomus discolor, in a social roosting context. Based on visual examination of spectrograms and subsequent quantitative analysis of syllables, eight distinct syllable classes were defined, and their prevalence in different behavioral contexts was examined. Four more syllable classes were observed in low numbers and are described here as well. These results show that P. discolor possesses a rich vocal repertoire, which includes vocalizations comparable to previously reported repertoires of other bat species as well as vocalizations previously undescribed. Our data provide detailed information about the temporal and spectral characteristics of syllables emitted by P. discolor, allowing for a better understanding of the communicative system and related behaviors of this species. Furthermore, this vocal repertoire will serve as a basis for future research using P. discolor as a model organism for vocal communication and vocal learning and it will allow for comparative studies between bat species.